Developing HIV assisted partner notification services tailored to Mexican key populations: a qualitative approach - Heleen Vermandere; Santiago Aguilera-Mijares; Liliane Martínez-Vargas; M. Arantxa Colchero; Sergio Bautista-Arredondo (BMC, 2021)
Abstract Background Assisted partner notification services (APNS) may increase HIV testing, early diagnosis, and treatment, but they are not formally implemented in Mexico, where the HIV epidemic is concentrated in men who have sex with men (MSM) and transwomen (TW). This study aimed to explore the awareness of and need for HIV partner notification, as well as to outline potential strategies for APNS based on identified barriers and facilitators. Methods We conducted semi-structured interviews to explore partner notification with MSM, TW, and counselors. Afterwards, brainstorm sessions were carried out to produce strategies for implementing APNS. Results Most participants reported experiences with informal partner notification and serostatus disclosure, but not with APNS. Only one counselor indicated assisting notification systematically. The main barriers for notifying or disclosing mentioned by both MSM and TW included fear of (violent) reactions, discrimination and lacking contact information of casual partners. Participants thought it was easier to inform a formal partner, conditional of being well informed about HIV. Given current stigma and lack of awareness, it was suggested that APNS should be preceded by HIV awareness efforts, and be provided by counselors or peers to mitigate potential rejection or violent reactions. Conclusions While APNS are not formally implemented in Mexico, all participants supported the service, indicating that APNS could potentially enhance early HIV diagnosis in Mexico. Strategies to implement such services need to be flexible addressing the individual needs of participants, guaranteeing the safety of more vulnerable participants.